Facile control of surfactant lamellar phase transition and adsorption behavior. Issue 31 (11th May 2020) - Gonçalves, Rui A.; Naidjonoka, Polina; Nylander, Tommy; Miguel, Maria G.; Lindman, Björn; Lam, Yeng Ming
Abstract : The presence of small water-soluble additives makes it possible to tune the surfactant gel-to-liquid crystalline (Lβ –Lα ) phase transition temperature ( T m ) for a bilayer-forming cationic surfactant system and its phase behavior on dilution. Abstract : This study sets out to investigate the effect of the presence of small water-soluble additives on the tunability of the surfactant gel-to-liquid crystalline (Lβ –Lα ) phase transition temperature ( T m ) for a bilayer-forming cationic surfactant and the phase behavior of such surfactant systems on dilution. This is strongly driven by the fact that this type of cationic surfactant has many interesting unanswered scientific questions and has found applications in various areas such as consumer care, the petrochemical industry, food science, etc. The underlying surfactant/additive interactions and the interfacial behavior of lamellar surfactant systems including the surfactant deposition on surfaces can provide new avenues to develop novel product formulations. We have examined dioctadecyldimethyl ammonium chloride (DODAC) in the presence of small polar additives, with respect to the phase behavior upon dilution and the deposition on silica. Differential scanning calorimetry (DSC) is used to track the transition temperature, T m, and synchrotron and laboratory-based small and wide-angle X-ray scattering (SAXS and WAXS) were used to determine the self-assembled surfactant structure below and above the T m . DSC scans showed that upon dilution the additives could be removed from the surfactant bilayer which in turn tuned the T m . A spontaneous transition from a liquid crystalline (Lα ) phase to a gel (Lβ ) phase on dilution was demonstrated, which indicated that additives could be taken out from the Lα phase. By means of in situ null ellipsometry, the deposition of a diluted surfactant Lβ phase upon replacement of bulk solution by deionized water was followed. This technique enables time-resolved monitoring of the deposited surfactant layer thickness and adsorbed amount, which allows us to understand the deposition on surfaces. Robust layers at least one bilayer-thick were deposited onto the surface and shown to be irreversibly adsorbed due to poor surfactant solvency in water. The thickest layer of surfactant deposited after dilution was found for mixtures with small amounts of additive since high amounts might lead to a phase-separated system.